PEMANFAATAN BLACKBERRY MESSENGER PADA KANTOR NOTARIS DI KOTA BATAM - Fifi Fifi (Universitas Putera Batam, 2015)
Slowly advances in information technology communication has entered into working life. The high will need a digital information service that people want to make different kinds of technological devices such as Black Berry Messenger selling well. This is because the ability in the spread of information and communication easy, practical, effective and efficient time. In the legal world, especially notaries in addition to following the legal developments as pillars, the development of the digital world also shall be followed as a means of support. Based on the research use blackberry messenger can know that on average the highest percentage answer renponden agree with the use of blackberry utilization of 47.20 percent, followed by 30.80% strongly agree. While the average of respondents who strongly disagree with the use blackberry messenger of 1.60 percent.